Sodium-rich fluorine-doped sodium iron pyrophosphate composite material and preparation method and application thereof
By introducing excess sodium and doped fluorine into the sodium ferric phosphate material, a sodium-rich fluorine-doped sodium ferric phosphate composite material was prepared, which solved the problems of low discharge specific capacity and poor cycle stability in sodium ion batteries in NFPP materials, and significantly improved the electrochemical performance of the material.
Patent Information
- Application Number
- CN202310280738.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-21
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2043-03-21
AI Technical Summary
The existing sodium ferric phosphate pyrophosphate (NFPP) materials have lower discharge specific capacity and poor circulation stability in sodium ion batteries.
NaxFe3.0(PO4)2P2O7Fy/C composite material is prepared by introducing excess sodium and doping a certain amount of fluorine into the material. The preparation method of the material includes mixing phosphate, iron salt, sodium salt, fluoride and carbon sources in deionized water, followed by heat treatment under an inert reduction atmosphere.
The discharge specific capacity and cycle stability of the material are improved. The first-round Coulomb efficiency of sodium ion batteries can reach 96.3%, and the capacity retention rate after 500 cycles can reach 92.0%, which has significantly improved performance.
Smart Images

Figure CN116281922B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of sodium ion batteries, and in particular to a sodium-rich fluorine-doped sodium iron pyrophosphate composite material, a preparation method and an application thereof. Background Art
[0002] With the continuous deterioration of global environmental problems and the intensification of the energy crisis, people are in urgent need of clean and renewable energy. In recent years, market demand has continuously driven the energy storage field towards electrochemical energy storage. Compared with traditional lithium-ion battery positive electrode materials such as lithium cobalt oxide, lithium manganese oxide, and ternary materials, sodium-ion battery positive electrode materials sodium iron pyrophosphate (Na4Fe3(PO4)2P2O7, denoted as NFPP) have the advantages of abundant reserves, wide distribution, low price, and stable structure. This feature fits the characteristics of large-scale energy storage devices. Therefore, sodium-ion batteries are considered to be one of the potential candidates for large-scale energy storage systems.
[0003] Sodium iron pyrophosphate (NFPP) has a high theoretical capacity (~129 mAh / g), a high operating voltage (~3.1 V, Na+ / Na) and a low volume expansion (~4%), and is considered to be the most promising cathode material for sodium ion batteries. However, when the existing NFPP materials are used in sodium ion batteries, the discharge specific capacity is low and the cycle stability is poor.
[0004] In view of this, the present invention is proposed. Summary of the invention
[0005] One of the purposes of the present invention is to provide a sodium-rich fluorine-doped sodium iron pyrophosphate composite material, aiming to solve the technical problems of low discharge specific capacity and poor cycle stability caused by the positive electrode material in sodium ion batteries in the prior art.
[0006] The second object of the present invention is to provide a method for preparing a sodium-rich fluorine-doped sodium iron pyrophosphate composite material.
[0007] The third object of the present invention is to provide a sodium-rich fluorine-doped sodium iron pyrophosphate composite material for use in a sodium ion positive electrode.
[0008] In order to solve the above technical problems, the present invention particularly adopts the following technical solutions:
[0009] The first aspect of the present invention provides a sodium-rich fluorine-doped sodium iron pyrophosphate composite material, the molecular formula of the composite material is Na x Fe 3.0 (PO4)2P2O7F y / C;
[0010] Among them, 4<x≤4.1, 0<y≤0.1.
[0011] Furthermore, the composite material has a particle size of 50 nm-10 μm, preferably 3 μm-5 μm.
[0012] The second aspect of the present invention provides a method for preparing the sodium-rich fluorine-doped sodium iron pyrophosphate composite material, comprising the following steps:
[0013] A. Add phosphate, iron salt, sodium salt, fluoride and carbon source to deionized water respectively, stir evenly to obtain a mixed solution, and dry the mixed solution to obtain a mixed precursor;
[0014] B. Heat treating the mixed precursor under an inert reducing atmosphere to obtain the sodium-rich fluorine-doped sodium iron pyrophosphate composite material.
[0015] Furthermore, the phosphate includes at least one of sodium dihydrogen phosphate, diammonium hydrogen phosphate and ammonium dihydrogen phosphate, preferably a compound of sodium dihydrogen phosphate and diammonium hydrogen phosphate.
[0016] The iron salt includes at least one of ferrous acetate, ferrous nitrate, ferrous oxalate and ferrous sulfate, preferably ferrous nitrate and ferrous acetate.
[0017] The sodium salt includes at least one of sodium dihydrogen phosphate, sodium carbonate, sodium bicarbonate, sodium acetate, sodium oxalate and sodium citrate, preferably sodium dihydrogen phosphate and sodium citrate.
[0018] The fluoride includes sodium fluoride and / or ammonium fluoride.
[0019] The carbon source comprises at least one of starch, citric acid, sucrose and glucose, preferably citric acid.
[0020] Further, the molar ratio of phosphate, iron salt, sodium salt and fluoride is 2:2.9-3:4-4.1:0-0.1;
[0021] Wherein, the added amount of the fluoride is not 0.
[0022] Furthermore, the molar ratio of phosphate, iron salt, sodium salt and fluoride is 2:2.99:4.01:0.01.
[0023] Further, the heat treatment includes pre-sintering followed by high-temperature calcining;
[0024] The pre-calcination is carried out by heating the temperature to 250°C-350°C at a heating rate of 1°C / min-5°C / min and then keeping the temperature for 3h-10h.
[0025] Preferably, the pre-calcination is carried out by heating the temperature to 300° C. at a heating rate of 2° C. / min and then keeping the temperature for 6 hours.
[0026] The high temperature calcination is carried out by heating the temperature to 450°C-550°C at a heating rate of 1°C / min-5°C / min and then keeping the temperature for 5h-15h.
[0027] Preferably, the high temperature calcination is carried out by heating the temperature to 500° C. at a heating rate of 2° C. / min and then keeping the temperature for 10 hours.
[0028] Furthermore, the inert reducing gas includes at least one of nitrogen, argon and hydrogen, and is preferably a mixture of argon and hydrogen.
[0029] Furthermore, in the mixed gas of argon and hydrogen, the volume proportion of hydrogen is 5%.
[0030] Furthermore, the carbon source accounts for 1wt.%-10wt.%, preferably 5wt.%.
[0031] Among them, the proportion of the carbon source is the proportion of the carbon source in the sodium-rich fluorine-doped sodium iron pyrophosphate composite material.
[0032] Furthermore, in step A, the drying method includes spray drying or freeze drying.
[0033] The third aspect of the present invention provides the use of the sodium-rich fluorine-doped sodium iron pyrophosphate composite material in the positive electrode of a sodium ion battery.
[0034] Preferably, the positive electrode of the sodium ion battery is prepared by dissolving the sodium-rich fluorine-doped sodium iron pyrophosphate composite material, acetylene black and a binder in a solvent to form a slurry, which is then coated on an aluminum foil and dried to obtain the positive electrode.
[0035] Compared with the prior art, the present invention has at least the following beneficial effects:
[0036] The sodium-rich fluorine-doped sodium iron pyrophosphate composite material provided by the present invention improves the discharge specific capacity of the material by introducing excess sodium; at the same time, the doping of anionic fluorine maintains the charge conservation of the material, reduces the migration energy barrier of sodium ions during the charge and discharge process, improves the kinetic performance of the system, and thus improves the cycle stability of the material. When it is applied to sodium ion batteries, the first cycle coulomb efficiency of the sodium ion battery can reach 96.3%, and the capacity retention rate after 500 cycles can reach 92.0%, and the performance has been significantly improved and enhanced.
[0037] The method for preparing the sodium-rich fluorine-doped sodium iron pyrophosphate composite material provided by the invention has continuous process, simple operation, high degree of mechanization, and is suitable for large-scale industrial application.
[0038] The application provided by the present invention provides a positive electrode material with high discharge specific capacity and better cycle stability for sodium ion batteries, promotes the development of sodium ion batteries towards high energy density and small volume, and promotes the rapid development of the downstream industrial chain. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0040] Figure 1 This is the SEM image obtained for Test Example 1;
[0041] Figure 2 This is the XRD pattern obtained in Test Example 2. DETAILED DESCRIPTION
[0042] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. The components of the embodiments of the present invention described and shown herein can be arranged and designed in various different configurations.
[0043] The first aspect of the present invention provides a sodium-rich fluorine-doped sodium iron pyrophosphate composite material, the molecular formula of the composite material is Na x Fe 3.0 (PO4)2P2O7F y / C;
[0044] Among them, 4<x≤4.1, 0<y≤0.1.
[0045] The sodium-rich fluorine-doped sodium iron pyrophosphate composite material provided by the present invention improves the discharge specific capacity of the material by introducing excess sodium; at the same time, the doping of anionic fluorine maintains the charge conservation of the material, reduces the migration energy barrier of sodium ions during the charge and discharge process, improves the kinetic performance of the system, and thus improves the cycle stability of the material. When it is applied to sodium ion batteries, the first cycle coulomb efficiency of the sodium ion battery can reach 96.3%, and the capacity retention rate after 500 cycles can reach 92.0%, and the performance has been significantly improved and enhanced.
[0046] In some embodiments of the present invention, the molecular formula of the composite material is typically but not limited to Na 4.1 Fe 3.0 (PO4)2P2O7F0.1 / C、Na 4.01 Fe 3.0 (PO4)2P2O7F 0.01 / C or Na 4.05 Fe 3.0 (PO4)2P2O7F 0.05 / C.
[0047] Further, the composite material has a particle size of 50nm-10μm, preferably 3μm-5μm. In some embodiments of the present invention, the composite material has a particle size of typically but not limited to 50nm, 100nm, 500nm, 1μm, 3μm, 5μm or 10μm.
[0048] The second aspect of the present invention provides a method for preparing the sodium-rich fluorine-doped sodium iron pyrophosphate composite material, comprising the following steps:
[0049] A. Add phosphate, iron salt, sodium salt, fluoride and carbon source to deionized water respectively, stir evenly to obtain a mixed solution, and dry the mixed solution to obtain a mixed precursor;
[0050] B. Heat treating the mixed precursor under an inert reducing atmosphere to obtain the sodium-rich fluorine-doped sodium iron pyrophosphate composite material.
[0051] The method for preparing the sodium-rich fluorine-doped sodium iron pyrophosphate composite material provided by the invention has continuous process, simple operation, high degree of mechanization, and is suitable for large-scale industrial application.
[0052] Furthermore, the phosphate includes at least one of sodium dihydrogen phosphate, diammonium hydrogen phosphate and ammonium dihydrogen phosphate, preferably a compound of sodium dihydrogen phosphate and diammonium hydrogen phosphate.
[0053] The iron salt includes at least one of ferrous acetate, ferrous nitrate, ferrous oxalate and ferrous sulfate, preferably ferrous nitrate and ferrous acetate.
[0054] The sodium salt includes at least one of sodium dihydrogen phosphate, sodium carbonate, sodium bicarbonate, sodium acetate, sodium oxalate and sodium citrate, preferably sodium dihydrogen phosphate and sodium citrate.
[0055] The fluoride includes sodium fluoride and / or ammonium fluoride.
[0056] The carbon source comprises at least one of starch, citric acid, sucrose and glucose, preferably citric acid.
[0057] Further, the molar ratio of phosphate, iron salt, sodium salt and fluoride is 2:2.9-3:4-4.1:0-0.1;
[0058] Wherein, the added amount of the fluoride is not 0.
[0059] In some embodiments of the present invention, the molar ratio of phosphate, iron salt, sodium salt and fluoride is typically but not limited to 2:2.9:4:0.01, 2:2.9:4:0.05, 2:2.9:4:0.1, 2:2.9:4.1:0.01, 2:2.9:4.1:0.05 or 2:2.9:4.1:0.1.
[0060] Furthermore, the molar ratio of phosphate, iron salt, sodium salt and fluoride is 2:2.99:4.01:0.01.
[0061] Further, the heat treatment includes pre-sintering followed by high-temperature calcining;
[0062] The pre-calcination is carried out by heating the temperature to 250°C-350°C at a heating rate of 1°C / min-5°C / min and then keeping the temperature for 3h-10h.
[0063] Preferably, the pre-calcination is carried out by heating the temperature to 300° C. at a heating rate of 2° C. / min and then keeping the temperature for 6 hours.
[0064] The high temperature calcination is carried out by heating the temperature to 450°C-550°C at a heating rate of 1°C / min-5°C / min and then keeping the temperature for 5h-15h.
[0065] Preferably, the high temperature calcination is carried out by heating the temperature to 500° C. at a heating rate of 2° C. / min and then keeping the temperature for 10 hours.
[0066] Furthermore, the inert reducing gas includes at least one of nitrogen, argon and hydrogen, and is preferably a mixture of argon and hydrogen.
[0067] Furthermore, in the mixed gas of argon and hydrogen, the volume proportion of hydrogen is 5%.
[0068] Furthermore, the carbon source accounts for 1wt.%-10wt.%, preferably 5wt.%. When the carbon source accounts for less than 1wt.%, the composite material has low overall electronic conductivity due to the presence of polyanion phosphate and pyrophosphate, which affects its electrochemical performance; when the carbon source accounts for more than 10wt.%, the carbon source as an inactive substance accounts for too high a proportion in the composite material, which reduces the overall energy density of the positive electrode material and is not conducive to the practical application of the material.
[0069] In some embodiments of the present invention, the proportion of the carbon source is typically but not limited to 1 wt.%, 2 wt.%, 3 wt.%, 4 wt.%, 5 wt.%, 6 wt.%, 7 wt.%, 8 wt.%, 9 wt.% or 10 wt.%.
[0070] Among them, the proportion of the carbon source is the proportion of the carbon source in the sodium-rich fluorine-doped sodium iron pyrophosphate composite material.
[0071] Furthermore, in step A, the drying method includes spray drying or freeze drying.
[0072] The third aspect of the present invention provides the use of the sodium-rich fluorine-doped sodium iron pyrophosphate composite material in the positive electrode of a sodium ion battery.
[0073] The application provided by the present invention provides a positive electrode material with high discharge specific capacity and better cycle stability for sodium ion batteries, promotes the development of sodium ion batteries towards high energy density and small volume, and promotes the rapid development of the downstream industrial chain.
[0074] Preferably, the positive electrode of the sodium ion battery is prepared by dissolving the sodium-rich fluorine-doped sodium iron pyrophosphate composite material, acetylene black and a binder in a solvent to form a slurry, which is then coated on an aluminum foil and dried to obtain the positive electrode.
[0075] In the following, some embodiments of the present invention are described in detail in conjunction with the embodiments. In the absence of conflict, the following embodiments and the features in the embodiments can be combined with each other. The raw materials used in the present invention can be obtained by commercial purchase unless otherwise specified.
[0076] Example 1
[0077] This embodiment provides a sodium-rich fluorine-doped sodium iron pyrophosphate composite material, taking 1.5mmol ferric nitrate nonahydrate, 1.002mol citric acid, 2mmol anhydrous sodium dihydrogen phosphate, and 0.05mmol sodium fluoride and dissolving them in deionized water. After spray drying, a precursor powder is obtained. The precursor powder is heated to 250°C in a tubular vacuum furnace and kept warm for 10 hours, and then heated to 450°C and kept warm for 15 hours. The whole process is protected by argon hydrogen mixed gas, and the volume content of hydrogen is 5%. The heating rate of the heating process is 1°C / min. After cooling with the furnace, the required Na 4.1 Fe3(PO4)2P2O7F 0.1 / C positive electrode composite material.
[0078] Example 2
[0079] This embodiment provides a sodium-rich fluorine-doped sodium iron pyrophosphate composite material, taking 1.5mmol ferric nitrate nonahydrate, 1.002mol citric acid, 2mmol anhydrous sodium dihydrogen phosphate, and 0.005mmol sodium fluoride and dissolving them in deionized water. After spray drying, a precursor powder is obtained. The precursor powder is heated to 300°C in a tubular vacuum furnace and kept warm for 6 hours, and then heated to 500°C and kept warm for 10 hours. The whole process is protected by argon hydrogen mixed gas, and the volume content of hydrogen is 5%. The heating rate of the heating process is 2°C / min. After cooling with the furnace, the required Na 4.01Fe3(PO4)2P2O7F 0.01 / C positive electrode composite material.
[0080] Example 3
[0081] This embodiment provides a sodium-rich fluorine-doped sodium iron pyrophosphate composite material, 1.5mmol ferric nitrate nonahydrate, 1.002mol citric acid, 2mmol anhydrous sodium dihydrogen phosphate, 0.025mmol sodium carbonate, 0.025mmol ammonium fluoride are dissolved in deionized water. After spray drying, a precursor powder is obtained. The precursor powder is heated to 350°C in a tubular vacuum furnace and kept warm for 3 hours, and then heated to 550°C and kept warm for 5 hours. The whole process is protected by argon hydrogen mixed gas, and the volume content of hydrogen is 5%. The heating rate of the heating process is 5°C / min. After cooling with the furnace, the required Na 4.05 Fe3(PO4)2P2O7F 0.05 / C positive electrode composite material.
[0082] Example 4
[0083] This embodiment provides a sodium-rich fluorine-doped sodium iron pyrophosphate composite material, taking 1.5mmol ferric nitrate nonahydrate, 1.002mol citric acid, 1mmol anhydrous sodium dihydrogen phosphate, 1.002mmol sodium citrate, and 0.01mmol sodium fluoride and dissolving them in deionized water. After spray drying, a precursor powder is obtained. The precursor powder is heated to 300°C in a tubular vacuum furnace and kept warm for 6 hours, and then heated to 500°C and kept warm for 10 hours. The whole process is protected by argon hydrogen mixed gas, and the volume content of hydrogen is 5%. The heating rate of the heating process is 2°C / min. After cooling with the furnace, the required Na 4.024 Fe3(PO4)2P2O7F 0.02 / C positive electrode composite material.
[0084] Comparative Example 1
[0085] This comparative example provides a sodium iron pyrophosphate composite material with a chemical formula of Na4Fe3(PO4)2P2O7 / C, which is self-made by the company. The preparation method is shown in Example 2, except that sodium fluoride is not added during the preparation process.
[0086] Test Example 1
[0087] The Na obtained in Example 2 4.01 Fe3(PO4)2P2O7F 0.01 / C cathode composite material was subjected to scanning electron microscopy (FESEM, JSM-6700F), and the images obtained are as follows Figure 1 shown.
[0088] like Figure 1 As shown, Na4.01 Fe3(PO4)2P2O7F 0.01 The / C cathode composite material is generally spherical particles with a wide distribution range of particle sizes, ranging from 50nm to 10μm, but mainly concentrated between 3μm and 5μm. 4.01 Fe3(PO4)2P2O7F 0.01 / C positive electrode composite material, the morphology is mainly spherical, and the size distribution is wide, but overall, it is mainly concentrated between 3μm and 5μm, and the particle size is relatively small.
[0089] Test Example 2
[0090] The Na obtained in Example 2 4.01 Fe3(PO4)2P2O7F 0.01 The / C cathode composite material was subjected to X-ray diffraction (SHIMADZU XRD-7000) test. The experimental conditions were as follows: copper target (λ = 0.1518nm), 2θ angle range of 5° to 70°. The XRD spectrum is shown in Figure 2 shown.
[0091] from Figure 2 It can be seen from the XRD pattern that Na 4.01 Fe3(PO4)2P2O7F 0.01 The / C cathode composite material has a pure phase crystal structure of Pn21a space group with high crystallinity (PDF standard card number: PDF#89-0579). No obvious impurity diffraction peaks were observed, indicating that the addition of a small amount of excess sodium ions, partial doping of fluorine elements, and coating of a certain carbon layer did not affect the crystal structure of the material. The results show that this experimental method can prepare a pure phase and highly crystalline sodium-rich fluorine-doped sodium iron pyrophosphate composite cathode material.
[0092] Test Example 1
[0093] Take 0.4g of the positive electrode composite material provided in Examples 1-4 and Comparative Example 1, 0.05g of the conductive agent (acetylene black), and 0.05g of the binder polyvinylidene fluoride (PVDF), and mix them in 0.5g of N-methylpyrrolidone (NMP) to obtain the required positive electrode slurry. Subsequently, the above slurry is coated on the treated aluminum foil and dried in a vacuum drying oven at 90°C for 10h to obtain the positive electrode plate. The above plate and sodium plate are assembled into a button battery in a glove box. The electrolyte is 1mol·L -1 The sodium salt of NaClO4 was dissolved in a solution of ethylene carbonate (EC) and ethylene methyl carbonate (EMC) in a volume ratio of 1:1, and 5% fluoroethylene carbonate (FEC) additive was added to the electrolyte. Subsequent electrochemical performance tests will focus on button cells.
[0094] The button cell was subjected to charge and discharge tests. The current 1C was 129 mA / g, and the charge and discharge temperature was room temperature. The charge and discharge specific capacity and first cycle coulomb efficiency of the button cell were measured, and the results are shown in Table 1.
[0095] Table 1
[0096]
[0097] As can be seen from Table 1, the electrochemical performance of Comparative Example 1 is the worst, with a first-cycle charge capacity of 109.8 mAh / g, a discharge capacity of 102.6 mAh / g, and a coulombic efficiency of 93.4%; after sodium-rich fluorine doping modification (Examples 1-4), the electrochemical performance is improved. Among them, Example 2 has the best electrochemical performance, with a first-cycle charge capacity of 115.7 mAh / g, a discharge capacity of 111.5 mAh / g, and a coulombic efficiency of 96.3%. This series of data fully illustrates that the sodium-rich fluorine doping modification method has a significant improvement in the electrochemical performance of the material, especially in the discharge capacity and coulombic efficiency. This is mainly because a moderate amount of sodium is introduced in the material preparation process, which increases the sodium ion content without destroying the material structure, thereby effectively improving the discharge capacity of the material.
[0098] Test Example 2
[0099] The button cell obtained in Experimental Example 1 was subjected to a cycle performance test. The current 1C was 129 mA / g, and the charge and discharge temperature was room temperature. Before the 1C formal cycle, it was activated with a small current of 0.1C for 3 cycles. The discharge specific capacity of the button cell was measured, and the discharge specific capacity was continued to be measured after 500 cycles, and the capacity retention rate was calculated. The results are shown in Table 2.
[0100] Table 2
[0101]
[0102] As can be seen from Table 2, the electrochemical performance of Comparative Example 1 is the worst, with an initial discharge capacity of 92.5 mAh / g at 1C, a discharge capacity of 77.3 mAh / g after 500 cycles, and a capacity retention rate of 83.5%; after sodium-rich fluorine doping modification (Examples 1-4), the electrochemical performance is improved. Among them, Example 2 has the best electrochemical performance, with an initial discharge capacity of 94.0 mAh / g at 1C of the sample of Example 2, a discharge capacity of 86.5 mAh / g after 500 cycles, and a capacity retention rate of 92.0%. This series of data fully demonstrates that the sodium-rich fluorine doping modification method has a significant improvement in the long-cycle stability of the material. This is mainly because the doping of anionic fluorine maintains the charge conservation of the material, reduces the migration energy barrier of sodium ions during the charge and discharge process, and improves the kinetic performance of the system, thereby improving the cycle stability of the material.
[0103] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A sodium-rich fluorine-doped sodium iron pyrophosphate composite material, characterized in that: The molecular formula of the composite material is Na x Fe 3.0 (PO4)2P2O7F y / C; Among them, 4<x≤4.1, 0<y≤0.
1.
2. The sodium-rich fluorine-doped sodium iron pyrophosphate composite material according to claim 1, characterized in that: The particle size of the composite material is 50nm-10μm.
3. The method for preparing the sodium-rich fluorine-doped sodium iron pyrophosphate composite material according to claim 1 or 2, characterized in that: The following steps are involved: A. Add phosphate, iron salt, sodium salt, fluoride and carbon source to deionized water respectively, stir evenly to obtain a mixed solution, and dry the mixed solution to obtain a mixed precursor; B. Heat treating the mixed precursor under an inert reducing atmosphere to obtain the sodium-rich fluorine-doped sodium iron pyrophosphate composite material.
4. The preparation method according to claim 3, characterized in that: The phosphate includes at least one of sodium dihydrogen phosphate, diammonium hydrogen phosphate and ammonium dihydrogen phosphate; The iron salt comprises at least one of ferrous acetate, ferrous nitrate, ferrous oxalate and ferrous sulfate; The sodium salt comprises at least one of sodium dihydrogen phosphate, sodium carbonate, sodium bicarbonate, sodium acetate, sodium oxalate and sodium citrate; The fluoride includes sodium fluoride and / or ammonium fluoride; The carbon source includes at least one of starch, citric acid, sucrose and glucose.
5. The preparation method according to claim 3, characterized in that: The molar ratio of phosphate, iron salt, sodium salt and fluoride is 2:2.9-3:4-4.1:0-0.1; Wherein, the added amount of the fluoride is not 0.
6. The preparation method according to claim 3, characterized in that: The molar ratio of phosphate, iron salt, sodium salt and fluoride is 2:2.99:4.01:0.
01.
7. The preparation method according to claim 3, characterized in that: The heat treatment includes pre-burning followed by high-temperature calcination; The pre-calcination is carried out by heating the temperature to 250°C-350°C at a heating rate of 1°C / min-5°C / min and then keeping the temperature for 3h-10h; The high temperature calcination is carried out by heating the temperature to 450°C-550°C at a heating rate of 1°C / min-5°C / min and then keeping the temperature for 5h-15h.
8. The preparation method according to claim 3, characterized in that: The carbon source accounts for 1wt.%-10wt.%; Among them, the proportion of the carbon source is the proportion of the carbon source in the sodium-rich fluorine-doped sodium iron pyrophosphate composite material.
9. The preparation method according to any one of claims 3 to 8, characterized in that: In step A, the drying method includes spray drying or freeze drying.
10. Use of the sodium-rich fluorine-doped sodium iron pyrophosphate composite material according to any one of claims 1 or 2 or the sodium-rich fluorine-doped sodium iron pyrophosphate composite material prepared by the preparation method according to any one of claims 3 to 8 in the positive electrode of a sodium ion battery.
Citation Information
Patent Citations
Doped sodium iron silicate electrode material and preparation method and application thereof
CN109607556A
All-iron-based sodium ion battery and preparation method thereof
CN115064695A